Safety leadership and safety citizenship behavior: the mediating roles of safety knowledge, safety motivation, and psychological contract of safety - Omidia, Leila; Karimi, Hossein; Pilbeam, Colin; Mousavi, Saeid; Moradi, Gholamreza (Taylor & Francis, 2025)
The relationship between safety leadership and safety citizenship behavior (SCB) is well established in prior research; however, the effects of safety knowledge, safety motivation, and psychological contract of safety (PCS) on this relationship still need to be examined. This study investigated the mediating roles of safety knowledge, safety motivation, and psychological contract of safety in the relationship between safety leadership and SCB. Cross-sectional survey data were gathered from 205 employees in a high-risk industry in Iran. Path analysis showed that safety knowledge, safety motivation, and PCS played mediating roles between safety leadership and SCB. Improving the safety of employees and enhancing safety in organizations can be achieved by considering the significance of safety leadership and enhancing SCB among employees. Creating environments with higher levels of fulfillment of safety obligations between leaders and employees is important in achieving safety goals.
Keywords: Safety leadership; safety citizenship behavior; safety knowledge; safety motivation; psychological contract of safety